PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 81 SINGKAWANG - Sari, Amanda Vita; Sunarsih, Eti; Marhayani, Dina Anika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the Student Teams Achievement Division (STAD) cooperative learning model to improve student learning outcomes in fourth-grade Pancasila Education at SDN 81 Singkawang. The background of this study is based on low student learning outcomes caused by conventional learning methods and a lack of active student involvement in the learning process. This study used a classroom action research (CAR) approach conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data collection techniques were conducted through observation, testing, and documentation. The results showed that the application of the STAD model can increase student activeness, cooperation, and understanding of Pancasila Education material. This is evident in the improvement in student learning outcomes in each cycle, both individually and in groups. Thus, the STAD cooperative learning model is effective in improving student learning outcomes, particularly in subjects that require an understanding of moral and national values such as Pancasila Education.